Mongolia : Second Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report, 2012)
This paper presents the second postprogram monitoring discussions on Mongolia's economic developments. The Mongolian economy is undergoing a rapid expansion underpinned by strong commodity prices. Macroeconomic policies have been too expansionary, and the economy is overheating. A steady erosion of fiscal discipline, set against a backdrop of heightened global economic risks, has raised the risk of macroeconomic instability. There is an urgent need to reorient policies to contain overheating and strengthen the economy's ability to endure deterioration in the global environment.